Thermal behavior of metallic and fiber cement tiles with simple and double layers - Almeida, Eduardo Alves [UNESP]; Souza, Fernando Augusto de [UNESP]; Furlan, Renato Luis [UNESP]; Pitelli Turco, Jose Eduardo [UNESP]; Milani, Adhemar Pitelli [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2018)
This research was conducted aiming to evaluate the thermal behavior of metallic and fiber cement tiles installed in simple and double layers. The experiment was performed on prototypes of roofing in single layers and double-spaced from 1.0 to 5.0 cm. It was used temperature sensors, installed on the inner surface of the roofing and in the center of the model for data collection. Data were analyzed using Skott-Knott test, considering the time of day, and roof type. The results showed that the spacing between tiles has an important influence on temperature gradient inside the prototype, been observed that double-spaced roofs, with 5.0 cm, showed the best results for metallic and fiber cement tiles.
Keywords: ambience; building material; thermal efficiency; thermal insulation